2015
DOI: 10.1038/ncomms8820
|View full text |Cite
|
Sign up to set email alerts
|

Universal self-field critical current for thin-film superconductors

Abstract: For any practical superconductor the magnitude of the critical current density, Jc, is crucially important. It sets the upper limit for current in the conductor. Usually Jc falls rapidly with increasing external magnetic field, but even in zero external field the current flowing in the conductor generates a self-field that limits Jc. Here we show for thin films of thickness less than the London penetration depth, λ, this limiting Jc adopts a universal value for all superconductors—metals, oxides, cuprates, pni… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
141
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(173 citation statements)
references
References 59 publications
22
141
0
Order By: Relevance
“…This may well be understandable, at least in terms of traditional vortex models where the pinning microstructure is inescapably variable. However, building on previous work [6] we show here that, under self-field conditions (zero external field), this universal goal can be achieved using a London-Meissner model in which transport becomes dissipative when, for type I superconductors, the surface current density reaches the depairing magnitude, B c /(μ 0 λ) or, for type II superconductors, B c1 /(μ 0 λ). Here B c is the thermodynamic critical field, B c1 the lower critical field and λ is the London penetration depth.…”
Section: Introductionmentioning
confidence: 56%
See 2 more Smart Citations
“…This may well be understandable, at least in terms of traditional vortex models where the pinning microstructure is inescapably variable. However, building on previous work [6] we show here that, under self-field conditions (zero external field), this universal goal can be achieved using a London-Meissner model in which transport becomes dissipative when, for type I superconductors, the surface current density reaches the depairing magnitude, B c /(μ 0 λ) or, for type II superconductors, B c1 /(μ 0 λ). Here B c is the thermodynamic critical field, B c1 the lower critical field and λ is the London penetration depth.…”
Section: Introductionmentioning
confidence: 56%
“…As noted, the foundations of our approach were established recently. [6] We analyzed J c (sf) for thin films of half thickness, b ≈ λ, in terms of transport London currents for which dissipation commences when the global current density reaches, for type I superconductors:…”
Section: Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…We note that this compares well with the doping induced in other systems using ILs. 21 In an effort to better define the link between our measurements and the standard transport properties of YBCO, we made use of the recent work by Talantsev and Tallon, which links the self field critical current density of a broad spectrum of superconductors in thin film form with their London penetration depth k. 22 According to them, experimental data show that as long as the film is thinner than its penetration depth (in YBCO k > 100 nm), the self-field J c is simply H c;1 =k. Making use of the standard Ginzburg-Landau expression for H c;1 leads to J c ðsfÞ / k À3 .…”
mentioning
confidence: 99%
“…Type II superconductors are typically used for applications and they also can sustain only the finite currents. The maximum value of J c is related to the lower critical field H c1 as indicated in recent experiments studying the properties of current currying superconductors [93][94][95], where some universalities observed in a number of different families of superconductors with various symmetries of the order parameter have been pointed out. Among all, it has been shown that for thin films of thickness b less than the penetration depth λ, there exist a limiting value of the current J c which for type I superconductors is H c /λ, whereas for type II materials H c1 /λ, where H c1 is the lower critical field [93].…”
Section: Jhep10(2016)152mentioning
confidence: 99%